Innovation diffusion and ICT adoption in JAKIM halal certified company in Klang Valley / Malisa Mazlan - Mazlan, Malisa (2005)
Islam is growing in popularity around the globe, and also the public's awarene:ss of it is increasing at such a rate that can expect to see dramatic growth in all halal sectors (Hayati Hayatudin, 2005). Malaysia as the most developed Muslim country has raised the Malaysian companies' growth rapidly in producing halal products in the face of competitive trade envirormient that dominates the world economy. In order to dominate the halal global hub it is important for the Malaysia government in making Malaysian halal companies compete globally for competitive advantage. Information and communication technology (ICT) has become the main substance in make those companies compete globally. Adopting ICT in the business can perceived benefits include increase a good quality of production, fast, profitability, productivity, reducing cost and much more. Therefore, this study was conducted to measure the extent of innovation diffusion and ICT adoption among JAKIM halal certified company in Klang Valley. Particularly for this research, self-administered questionnaires had been given to the companies in finding the primary data. The framework of IT Adoption Model which proposed by Rosziati Ibrahim and Minoi (2002) and portion of Rogers' model of innovation diffusion (1995) was used in this paper. Finding of the survey found that the companies have a high degree of adoption in the variables of relative advantage, compatibility, trialability, observability and complexity. A high degree of adoption in complexity variable indicates that they have a difficult and hard to adopting ICT in their business. Each of organizational parameters are independent on attitude toward innovation, mean that there is no different perception on attitude toward innovation to be associated to the organizational parameters.